Surface modification of polyacrylonitrile based ultrafiltration membrane - Lohokare, Harshada R.; Kumbharkar, S. C.; Bhole, Yogesh S.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2006)
Ultrafiltration membrane based on polyacrylonitrile prepared by phase inversion method using zinc chloride as an additive showed more than 90% rejection for BSA and 90-110 Im(-2) h(-1) water flux. The surface modification of this membrane was studied using ethanolamine, triethylamine, sodium hydroxide, and potassium hydroxide solutions. The effect of base treatment time and temperature on water flux and rejection was investigated. The membranes exhibited swelling by NaOH treatment followed by deswelling by HCl post-treatment, similar to pH responsive membranes. The treatment by organic as well as inorganic bases improved water flux with a slight lowering in BSA rejection by dead-end mode type treatment. A 230% increase in water flux was achieved by sodium hydroxide treatment in crossflow mode without a noticeable pore swelling by SEM. The contact angle of the modified membranes was decreased as compared to the unmodified one indicating appreciable surface modification. As the treatment time or temperature increased, the ESCA analysis showed increased population of Na-carboxylate groups. (c) 2006 Wiley Periodicals, Inc.
Keywords: BSA rejection; chemical treatment; polyacrylonitrile membrane; surface modification; Ultrafiltration

Solvent and pH-stable poly(2,5-benzimidazole) (ABPBI) based UF membranes: preparation and characterizations - Lohokare, Harshada R.; Chaudhari, Harshal D.; Kharul, Ulhas. K. (Journal of Membrane Science, 2018)
Poly(2,5-benzimidazole), commonly known as ABPBI, is an excellent thermo-chemically stable polymer that is widely evaluated as a proton exchange membrane material in a fuel cell. Its niche intrinsic characteristics could be highly useful in the membrane preparation for various separation applications, especially under harsher environments. To gain insights towards this feasibility, ABPBI based supported membranes were prepared by phase inversion method. Effects of the nonwoven porous support material (polypropylene/polyester), non-solvent (water/0.5 N NaOH) and polymer concentration (6 or 4 wt%) on the membrane properties (water flux, rejection and porosity) were investigated. The stability of these membranes towards common organic solvents, concentrated acid (25 N H2SO4), base (2.5 N NaOH) and an autoclave condition was analyzed. ABPBI membrane showed a pore collapse after drying. In order to avoid this, the glycerol treatment was not only found to be suitable but also repeatable, without significant deviations in the water flux.
Keywords: ABPBI membrane; Pore size distribution; Solvent stable membranes; Ultrafiltration